164k views
4 votes
2) -2(7n – 6) +n=-3 - 8n

2 Answers

6 votes

Answer:

n = 3

Explanation:


-2(7n-6)+n=-3-8n\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\(-2)(7n)+(-2)(-6)+n=-3-8n\\\\-14n+12+n=-3-8n\qquad\text{subtract 12 from both sides}\\\\(-14n+n)+12-12=-3-12-8n\\\\-13n=-15-8n\qquad\text{add}\ 8n\ \text{to both sides}\\\\-13n+8n=-15-8n+8n\\\\-5n=-15\qquad\text{divide both sides by (-5)}\\\\(-5n)/(-5)=(-15)/(-5)\\\\\huge\boxed{n=3}

User Alexandru Dranca
by
5.7k points
5 votes

Answer and Step-by-step explanation:

For this equation the answer is :
n=3

Step 1 : Simplify both the sides of the equation :


-2(7n-6)+n=-3-8n


(-2)(7n)+(-2)(-6)+n=-3+-8n (Distribute)


-14n+12+n=-3+-8n


(-14n+n)+(12)=-8n-3 (Combine the like terms)


-13n+12=-8n-3


-13n+12=-8n-3

Step 2 : Add "
8n" to both the sides :


-13n+12+8n=-8n-3+8n


-5n+12=-3

Step 3 : Subtract "
12" from both the sides :


-5n+12-12=-3-12


-5n=-15

Step 4 : Divide both the sides by "
-5"


(-5n)/(-5) =(-15)/(-5)


n=3

That's your final answer :
n=3

User Falanwe
by
5.5k points